2005
DOI: 10.1002/rcm.2082
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive quantification of urinary N7‐methylguanine by isotope‐dilution liquid chromatography/electrospray ionization tandem mass spectrometry with on‐line solid‐phase extraction

Abstract: A rapid, highly specific and sensitive isotope-dilution liquid chromatography/tandem mass spectrometry (LC/MS/MS) method coupled with an on-line solid-phase extraction (SPE) system was developed to measure N7-methylguanine (N7-MeG) in urine. 15N5-Labeled N7-MeG was synthesized to serve as an internal standard, and an on-line SPE cartridge was used for on-line sample cleanup and enrichment. The urine sample can be directly analyzed within 15 min without prior sample purification. The detection limit for this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…Urinary N7-MeG has been previously measured in smokers for assessing the exposure of tobacco-specific nitrosamines. We previously measured urinary N7-MeG among smokers and nonsmokers using LC-MS/MS and reported the mean urinary levels of 4,215 and 3,035 ng/mg creatinine for smokers and nonsmokers, respectively (16). Ichiba et al (44) also reported a mean urinary N7-MeG level of 4,600 ng/mg creatinine among smokers, a level that was found to be significantly decreased by 46% (2,500 ng/mg creatinine) after smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary N7-MeG has been previously measured in smokers for assessing the exposure of tobacco-specific nitrosamines. We previously measured urinary N7-MeG among smokers and nonsmokers using LC-MS/MS and reported the mean urinary levels of 4,215 and 3,035 ng/mg creatinine for smokers and nonsmokers, respectively (16). Ichiba et al (44) also reported a mean urinary N7-MeG level of 4,600 ng/mg creatinine among smokers, a level that was found to be significantly decreased by 46% (2,500 ng/mg creatinine) after smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary N7-MeG concentrations were measured using a published method of LC-MS/MS with on-line solid-phase extraction (16). Fifty microliters of urine were diluted 1,000 times with 96% acetonitrile containing 0.1% formic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate quantification of adducted bases at extremely low concentrations has frequently relied on the use of nonradioactive isotope-labeled standards to compensate for the loss of analyte during sample preparation, which has been the most critical step in eliminating the matrix effect for analysis of modified bases by MS (19 ). Furthermore, on-line sample extraction with a column-switching device is an extremely useful technique for automating the preparation of biological samples for LC-MS methods (20,21 ). Its advantages include less ion suppression and relatively short run times as well as higher sensitivity and selectivity, especially for urine samples containing a considerable amount of coeluting interferents.…”
mentioning
confidence: 99%
“…In order to seek more effective, environmental friendly, and economic enrichment materials for the application of on-line SPE analysis, many scholars pay attention on the development of new materials, including amino column [65] , hydrosulfonyl column [66] , copper isonicotinate coordination polymer [67] , -cyclodextrin silica gel [68] , polymer columns [69,70] , immunoaffinity column [71,72] , expanded graphite [73] , multi-walled carbon nanotube [74] , and some application even use cotton [75] and cigarette filter [76,77] for on-line adsorption of organic pollutants and perfect results could be obtained. The properties of these new adsorbents are low cost, easy producibility, some of which can be used repeatedly.…”
Section: Other Enrichment Materialsmentioning
confidence: 99%